An international comparison of voting by committees - Alexander Jung (European Central Bank (ECB), 2011)
This paper provides new empirical evidence on policy-makers' voting patterns on interest rates. Applying (pooled) Taylor-type rules and using real-time information available from published inflation reports and voting records, the paper tests for heterogeneity among committee members in three monetary policy committees: the FOMC, the Bank of England's MPC and the Riksbank's Executive Board. It separately estimates the empirical reaction functions with and without imposing the long-run restriction from the inertia, thereby distinguishing between the short-run and long-run responses of members to incoming information. Unconstrained reaction functions that measure the short-term response show that preference heterogeneity and some diversity of views on the inflation and economic outlook was present in all three committees. By contrast, constrained reaction functions that measure the long-term response find that evidence in favour of preference heterogeneity in all three committees is at best weak. Preference distributions in all three committees were fairly symmetric around the respective mean and diversity of views was only observed in the case of Sweden when including the financial crisis episode. A cluster analysis of the Riksbank's Executive Board, which only comprises internal members, confirms that its members have disperse preferences and views on the transmission mechanism. For the FOMC and for the MPC this analysis suggests that among several background characteristics (membership, background, tenure), membership is a potentially relevant factor that may explain some of the differences in preferences.
Keywords: C23; D72; D83; E58; 330; collective decision-making; heterogeneous preferences; monetary policy committee; pooled regressions; Taylor rule; voting behavior